Aesthetic Modes of Attack: The Woman Critic-Artist, Caractère unique - van Herk, Aritha (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
This paper explores how women who are both critics and artists resist the designations assigned to genre and gender. The alias of caractère unique subverts the academic categories that seek to locate and confine their unique practice and their work. In a set of creative evasions that explore the limitations of brackets and applications, this investigation of ambiguity proceeds as a poetics of digression, working from interviews that Dorota Filipczak conducted with Mieke Bal and Rukmini Bhaya Nair. The result is an excursion into bavardage that is nevertheless an aesthetic disruption of the authority of structure and destination.